6y-3=48x

Simple and best practice solution for 6y-3=48x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y-3=48x equation:


Simplifying
6y + -3 = 48x

Reorder the terms:
-3 + 6y = 48x

Solving
-3 + 6y = 48x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 6y = 3 + 48x

Combine like terms: -3 + 3 = 0
0 + 6y = 3 + 48x
6y = 3 + 48x

Divide each side by '6'.
y = 0.5 + 8x

Simplifying
y = 0.5 + 8x

See similar equations:

| b*7=10 | | 1.8r+9=-5.7r+6 | | 11(21m+10)=0 | | 9-2z=21 | | 5y-4=0 | | 3(-4+4n)=6+3n | | 8s-6=4s+44 | | 23+4z=31 | | 3(x-2)-4x=8 | | 4h+4=12 | | 9x+3y=-21 | | -2(n+7)=-15 | | 4a+45=90 | | 7b-24=4b | | 5x^2+5x-11=37-29x | | 2(y+4)-8y=-32 | | 7(2-1.4)=3(1.4) | | 3(a-2)=42 | | 0.14(2x-3)=3 | | 8+3(2x-1)= | | x^2+12-27=0 | | (2y+1)+(71-3y)+(3x+4y)=180 | | 3(n+4)=18+n | | -38=2(8b-3) | | 1.5+0.2t=2 | | 2j+10=4 | | 14+7m=3m | | 7(a+8)=49 | | 3x^2+17x+15=0 | | 9v=10-v | | -0.571a-9=1 | | 7x^2+8x-14=58-47x |

Equations solver categories